Reflexos de Tordesilhas numa nota antiportuguesa de Pedro Mártir de Anghiera - Osório, Jorge Alves (1994)
This article attempts to demonstrate that the end of Decade VIII of De Orbe Nouo by Pedro Martir de Anghiera (according to the 1530 edition) includes an anti-Portuguese note which reflects the political dispute between the two kingdoms of the Iberian Peninsula during the 15th and 16th centuries. The author also takes account of the notes in the margins of the copy of this work in the Oporto Public Library.